Dielectric properties of nanocrystalline barium zirconate titanate synthesized by glycine-nitrate autocombustion - Seeharaj, Panpailin; Charoonsuk, Thitirat; Vittayakorn, Naratip (My University, 2019)
Dielectric properties of nanocrystalline barium zirconate titanate (Ba(ZrxTi1-x)O3; BZT for x = 0.1 and 0.3) synthesized by glycine-nitrate autocombustion method were investigated in this study. The phase formation examined by TGA-DTA, XRD, FT-IR and Raman spectroscopy confirmed that high purity single-phase BZT with perovskite structure was obtained by using glycine-to-nitrate molar ratio of 2.2:4 and calcining in air at 1100 °C for 4 h. TEM analysis showed that BZT had agglomerate particles consisted of primary spherical nanocrystals with the size of 8-11 nm. The diffuse phase transition behavior of BZT ceramics increased with increasing Zr concentration and for x = 0.3, the Curie temperature; Tc, shifted to below room temperature. The BZT ceramics for x = 0.1 had relatively high dielectric constant (ε), 13007, low Tc, 76 °C and comparable dielectric loss (tan δ) at Tc, 0.012 which caused by the high degree of Zr diffuseness into the perovskite structure. These results suggest that glycine-nitrate autocombustion is the effective method for preparing high quality BZT ceramics.
Keywords: Autocombustion; barium zirconate titanate; dielectric property; glycine-nitrate